Komparasi Tampilan dan Hasil Lima Varietas Jagung Manis (Zea mays saccharata, Sturt) di Kota Pekanbaru - Surtinah Surtinah; Neng Susi; Sri Utami Lestari (Jurnal Ilmiah Pertanian, 2016)
The purpose of this study was to obtain sweet corn varieties that can be cultivated Pekanbaru. The method used is an experimental method to design treatment 5 varieties of sweet corn that is v1 = Sugar 75; v2 = Star Asia; v3 = Bonanza; v4 = Sagita sweet; v5 = Master sweet, and using a completely randomized design environment and repeated 6 times. Parameter observation is plant height, number of leaves, leaf length, leaf width, length cob without husk (cm), weight berkelobot cob, cob weight without berkelobot (g), and seed sugar content (%). The data obtained were analyzed using analysis of variance followed by DMRT multiple range test at 5%. Asia Star varieties are best varieties, followed by varetas sagita Sweet.